Why do companies purchase timely quarterly reviews? - Ettredge, Mike; Simon, Dan; Smith, David; Stone, Mary (Journal of Accounting and Economics, 1994)
The SEC encourages companies to have their quarterly financial information reviewed by an independent accountant prior to filing Forms 10-Q (i.e., timely review). Many companies, however, choose to have their quarterly data reviewed only at year-end. Companies contracting for timely reviews are hypothesized to be seeking a higher level of monitoring because of higher internal and external agency costs. Empirical analyses support this hypothesis. The likelihood that a company purchases timely reviews is significantly associated with several proxies for internal and external agency costs.